Pengaruh Terapi Birthball terhadap Kemajuan Persalinan Kala I pada Ibu Bersalin di Pustu Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Ribur Sinaga; Fitri Handayani; Nopalina Suyanti Damanik; Rumondang Sitorus; Nur Azizah; Kamelia Sinaga (Universitas Muhamadiyah Manado, 2024)
Birthball or birth ball can be used by mothers in the first stage of labor which is useful for helping the progress of labor. The advantages of using a birthball are that it can increase blood flow to the uterus, placenta and baby, and can increase the pelvic outlet, provide comfort for the knees and ankles, provide counter-pressure on the perineum and thighs, work with gravity that pushes the baby down so that it accelerates the process of opening and lowering the baby's head and the labor process can take place physiologically. This study aims to determine the Effect of Birthball Therapy on the Progress of Labor in the First Stage of Labor in Mothers in Bangun Rejo Health Center, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. The research design used is the Quasy Experiment Method (Experiment). By using the Two Group Design design, in this study the population was all mothers in labor as many as 20 people using the Mann-Whitney Test. The results of the study using the Man Whitney test to see the comparison between the intervention group and the control group obtained a sig value of 0.029 or <0.05 with a z table value of 2.189. So H0 is rejected and Ha is accepted, which means that there is an effect of birthball on the progress of the first stage in mothers who are given birthball therapy and those who are not given birthball therapy at Pustu Bangun Rejo, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. It is hoped that the research site will become a forum and facilitator for mothers in labor in facing a comfortable and enjoyable labor process in going through a shorter first stage.